Media Habit dan Interpretasi Anak Usia Dini Kota Bengkulu tentang Tayangan Media - Mrs Gushevinalti; Susri Adeni; Lely Arrianie (Program Studi Ilmu Komunikasi, 2014)
Generally, the message from television is not separated for the television viewers; it means that anyone can watch television programs. Children without any parental supervision can have a habit of consuming media where those television programs are not addressed to their age. This study aims to assess media habits or television viewing habits and media consumption patterns conducted by early childhood in the city of Bengkulu; the other goal is to decipher the meaning of the impressions of early childhood about the for children television shows as well as the shows for adults. This study is a qualitative study and conducted in early childhood or kindergarten students at TK Intan Insani dan PAUD Haqiqi in the city of Bengkulu. The main method of data collection is in-depth interviews and observation. Results reveal that media habits or television viewing habits and media consumption patterns conducted by early childhood in the city of Bengkulu is very high. The watching time for children is mostly 3 to 5 hours per a day. The term dating, falling in love, lover is a term that is understood through songs and sinetron or adult movies they watch. The interpretation of the child regarding special program in this study is illustrated naturally.